ANALISIS PENDAPATAN INDUSTRI RUMAH TANGGA PENYULINGAN MINYAK DAUN CENGKEH DI DESA PALAU KECAMATAN BALAESANG TANJUNG KABUPATEN DONGGALA - Arizona, Muh. Nur Hanief; Lamusa, Arifuddin (AGROTEKBIS, 2016)
Indonesia was a country which located at kebayoran the equator and tropics and two seasons. Variegated plants can grow well, in various areas there were plants which can be used as a source of oil producer volatile is no exception in central Sulawesi that is one producer cloves who leaves are a raw materials making volatile oil. Village Palau who is located in Kecamatan Balaesang Tanjung Donggala is one of the villages there is a oil production volatile leaves cloves. The purpose to be achieved in this study is to find the income from income home industry the distillation of volatile oil of the leaves cloves in the village of Palau. The location of this research ditentuan deliberately and implemented from home industry the distillation of volatile oil of the leaves cloves located in the village of Palau, Tanjung sub-district Balesang, Donggala, central Sulawesi province. The number of respondents in research are always two people namely business owners and employees to your production. An instrument the analysis used is an analysis of income. Based on the results of the data analysis and discussion then obtained a conclusion that is flattened income per month home industry volatile oil of the leaves cloves for five months the production process in the village of Rp. 5.450.654 Palau. The average oil production per month as many as 287.8 Kg.Â Key Words: Income , Home Industry, Volatile Oil Of The Leaves Cloves.